An Unusual Foetal Monster Calf with Double Eyes – A Case Report - Ghosh, Chhotan Kumar; Murmu, Susanta (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Foetal monstrosity is a disturbance of the development that involves various organs and systems that may cause great distortion of the individual (Vegad, 2007). Various types of foetal monsters in animals cannot be easily delivered and frequently needs caesarean section or fetotomy or forced traction that needs to be cautious (Sharma, 2006). This report deals with a rare case of double eyed hydrocephalic foetal monster calf with its morphological features.